IMPLEMENTATION OF SIMPLE ADDITIVE WEIGHTING (SAW) IN DECISION SUPPORT SYSTEMS AS A RECOMMENDATION FOR STUDENT CREATIVITY PROGRAM PROPOSALS - Raden Aris Sugianto; Muhammad Gunawan (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
This study aims to develop a decision support system that can facilitate the proposal selection process and provide an alternative ranking for the selection results of student creativity program proposal selection. This decision support system uses the simple additive weighting method calculation. The criteria used in this assessment refer to the 2020 Student Creativity Program Guidebook. The data used in this decision support system uses proposal selection data at the Student Creativity Development Unit at the Muhammadiyah University of North Sumatra in 2019 for 2020. This system was developed by determining criteria and weight determination using the Simple Additive Weighting method and determining the preference value of the predetermined criteria. Calculations using the Simple Additive Weighting Method certainly have advantages and disadvantages. The advantages of SAW with a simple and simple ranking process that can be applied to decision-making cases such as in the recommendation of selecting proposals with various attributes. By utilizing the advantages and disadvantages of the SAW method, this Decision Support System is able to produce an accuracy of 97%. This decision support system using the SAW method can help simplify the process of selecting proposals and provide alternative choices from the ranking results. Further research is suggested for the development of a decision support system for proposal selection using a combination of different methods between SAW and other methods.